Detection and Antibiogram of Different Bacterial Agents From Market Goat Meat (Research in Agriculture Livestock and Fisheries, 2021)
The study was conducted to detect various pathogenic as well as spoilage bacteria present in goat meats and also their antibiogram. Different body regions such as brisket, neck and thigh, supplied at different places like Krishi market, Mohakhali kacha bazar, and Charulata market within Dhaka City Corporation area, were taken and the bacteria were isolated. The isolated bacteria were identified on the basis of cultural, morphological, and biochemical characteristics. The isolated bacterial agents were: Staphylococcus spp., Escherichia coli, Bacillus spp., Micrococcus spp., Streptococcus spp., Enterobacter spp., Proteus spp., Citrobacter spp., Salmonella spp., and Pseudomonas spp. Antibiotic susceptibility test using disc diffusion method revealed that most of the isolates were found to be more or less resistant to tetracycline, ampicillin and erythromycin indicating that these may be a threat to consumer’s health. It is emphasized that the present sanitary conditions, as revealed through this study, of meat processing need to be improved so as to minimize microbial contamination. Suggestions are made to introduce Longitudinally Integrated Safety Assurance (LISA) system and Good Manufacturing Practices (GMP) principles.Res. Agric., Livest. Fish.8(1): 135-143, April 2021